Convergence of Physical Mathematics & the Universal Torus: Convergence of Physical Mathematics & the Universal Torus - Cusack, Paul T E (Asian Journal of Mathematical Sciences(AJMS), 2018)
Herein we consider the imaginary number and how it leads to the convergence of all mathematics, its ultimate purpose. The golden Mean is interplayed with geometry, and calculus, and linear algebra. We show that transcendental and trigonometries are important in the convergence of mathematics. Topology provides that the universe is a torus with the golden mean imbedded into it fabric. Finally, the physical universe parameters are considered as the proof of mathematical convergence.